Understanding mother-to-child transmission of HIV among mothers engaged in HIV care in Kenya: a case report - Emily L. Tuthill; Belinda C. Odhiambo; Ann E. Maltby (International Breastfeeding Journal, 2024)
Abstract Background Mother-to-child transmission of HIV, which may occur in utero, during birth, or through breastmilk, is now largely preventable with the advancement of HIV testing and treatment for women and their infants. Globally, great progress has been recorded over the years, with a 58% decline in new infections in children from 2010 to 2022. Currently, Kenya is among the countries with the highest rates of mother-to-child transmission of HIV despite consistent efforts to promote prevention of mother to child transmission strategies. Methods This case report presents the experiences of a woman, engaged in HIV care in Kenya, whose baby contracted HIV. The data used to describe this case come from surveys, provider notes, health records, observational notes, notes from phone call consultations, and one in-depth interview. All data sources were carefully reviewed, compared and complied to describe the timeline of events and context of the participant’s experience. Results We found multiple factors which may have contributed to this case of mother-to-child transmission of HIV. Antenatal care was initiated late in pregnancy (during the third trimester), and as a result, HIV diagnosis and treatment also occurred late in pregnancy. In addition, a lack of coordination between the clinic providing antenatal care and HIV treatment, and the hospital providing labor and delivery services led to breastfeeding initiation prior to the administration of infant HIV prophylaxis medications. Finally, poor maternal adherence to HIV medications went undetected and unaddressed until it was revealed by routine viral load monitoring three months after initiating HIV treatment (more than two months postpartum). Conclusions Our case report shows the continued need for more intensive and integrated care for mothers living with HIV and their infants including support for pregnant women newly diagnosed with HIV, coordination of perinatal and HIV care, provisions for routine monitoring of HIV medication adherence, intensive follow-up care including point of care testing for HIV exposed infants and in person breastfeeding support. Our case report contributes an important perspective especially in light of the current UNAIDS Global AIDS Strategy which recently inspired the Global Alliance to end AIDS in Children.